The role of behavior change communication on knowledge and uptake of postpartum contraception among antenatal mothers in Puducherry: a randomized controlled trial - Chauhan, Neelima S.; Mathew, Agnes (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: India accounts for world's 17.5 percent population and is the second most populous country in the world next only to China (19.4%). Birth control pills, condoms, sterilization, IUD (intrauterine device) etc. are most commonly practiced family planning methods in India. The latest NFHS shows that 77% of sterilized women did not use a family planning method. Despite of family welfare program having a target free approach, the program has not been successful in educating people about the concept and advantages of contraceptive methods for spacing births. Methods: This randomized controlled trial was carried out in the department of obstetrics and gynecology of Pondicherry Institute of Medical Sciences (PIMS), Puducherry. All antenatal mothers >28 weeks of gestational age were enrolled and given a semi-structured questionnaire. After randomization intervention was done in the form of counselling and distribution of pamphlets for future use. The women were followed in the postnatal period and 6 weeks later. Results: A total of 280 subjects were enrolled in this study. Socio-demographic characteristics were similar in both the study groups. Majority of women in both the comparison and intervention group were in the age group 20-25 years (43.6%). Very few participants (20.0%) had used some form of contraception to delay pregnancy. However, the postpartum follow-up of the study participants revealed significant increase in the knowledge on the various contraceptive methods in the intervention group compared with the comparison group. Conclusions: The implementation of behaviour change communication strategy to communicate the benefits of uptake of postpartum contraception to antenatal mothers, is vital in improving the acceptability of family planning programs in India.